PROMOTING A READING CULTURE AMONG UNIVERSITY STUDENTS - Shahobova Shahzoda Abdujamilovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
In  recent  years,  the  significance  of  reading  in  higher  education  has  drawn increasing attention from educators, researchers, and policymakers. A well-developed reading culture among students contributes not only to academic success but also to personal and professional development. This paper explores the current state of reading habits among university students and identifies the factors that influence their reading behavior.  Using  a  mixed-methods  approach,  including  surveys  and  interviews,  the study investigates both the challenges and opportunities in promoting a reading culture. The  findings  highlight  the  role  of  digital  technologies,  institutional  support,  peer influence, and individual motivation. The article concludes by recommending practical strategies that can be employed by educators and institutions to foster a sustainable and engaging reading environment.